Dependence of Adhesion Properties on Blend Ratio of Ethylene-Propylene-Diene Rubber/Standard Malaysian Rubber Blend Adhesive - Poh, B. T.; Lamaming, J.; Tay, G. S. (Hindawi Publishing Corporation, 2013)
Viscosity, tack and, peel and shear strengths of ethylene-propylene-diene rubber (EPDM)/standard Malaysian rubber (SMR L) blend adhesive were studied using various blend ratios of the two rubbers, ranging from 0 to 100% EPDM. Coumarone-indene resin, toluene, and poly(ethylene terephthalate) (PET) were used as the tackifier, solvent, and coating substrate, respectively. The tackifier content was fixed at 40 parts per hundred parts of rubber (phr). A SHEEN hand coater was used to coat the adhesive on PET film at four coating thicknesses, that is, 30, 60, 90, and 120